Differentiating axonal loss and demyelination in chronic MS lesions: A novel approach using single streamline diffusivity analysis - Klistorner, Samuel; Barnett, Michael H.; Wasserthal, Jakob; Yiannikas, Con; Barton, Joshua; Parratt, John; You, Yuyi; Graham, Stuart L.; Klistorner, Alexander (PloS one, 2021)
We describe a new single-streamline based approach to analyse diffusivity within chronic MS lesions. We used the proposed method to examine diffusivity profiles in 30 patients with relapsing multiple sclerosis and observed a significant increase of both RD and AD within the lesion core (0.38+/-0.09 μm 2 /ms and 0.30+/-0.12 μm 2 /ms respectively, p<0.0001 for both) that gradually and symmetrically diminished away from the lesion. T1-hypointensity derived axonal loss correlated highly with ΔAD (r = 0.82, p<0.0001), but moderately with ΔRD (r = 0.60, p<0.0001). Furthermore, the trendline of the ΔAD vs axonal loss intersected both axes at zero indicating close agreement between two measures in assessing the degree of axonal loss. Conversely, the trendline of the ΔRD function demonstrated a high positive value at the zero level of axonal loss, suggesting that even lesions with preserved axonal content exhibit a significant increase of RD. There was also a significant negative correlation between the level of preferential RD increase (ΔRD-ΔAD) in the lesion core and the degree of axonal damage (r = -0.62, p<0.001), indicating that ΔRD dominates in cases with milder axonal loss. Modelling diffusivity changes in the core of chronic MS lesions based on the direct proportionality of ΔAD with axonal loss and the proposed dual nature of ΔRD yielded results that were strikingly similar to the experimental data. Evaluation of lesions in a sizable cohort of MS patients using the proposed method supports the use of ΔAD as a marker of axonal loss; and the notion that demyelination and axonal loss independently contribute to the increase of RD in chronic MS lesions. The work highlights the importance of selecting appropriate patient cohorts for clinical trials of pro-remyelinating and neuroprotective therapeutics.